Samoefikasnost majki dece sa oštećenjem vida predškolskog uzrasta - Nikolić, Snežana; Vučinić, Vesna; Anđelković, Marija; Grbović, Aleksandra (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Maternal self-efficacy refers to a mother’s belief in her ability to effectively meet the demands of the parental role and positively influence her child’s development. Objective. The aim of this study is to examine the relationship between maternal self-efficacy among mothers of children with visual impairments and various sociodemographic characteristics (age, level of education, marital status, and employment status). Method. The sample consisted of 42 mothers of preschool-aged children with visual impairments and multiple disabilities who were enrolled in early intervention programs. Data were collected using the Early Intervention Parenting Self-Efficacy Scale (EIPSES). Results. Employment emerged as a significant factor in the self-efficacy of mothers of children with visual impairments and multiple disabilities. Employed mothers demonstrated a higher level of confidence in their ability to meet the demands of the parental role (p = .001), and simultaneously had higher expectations from support professionals (p = .006). No statistically significant relationship was found between perceived maternal self-efficacy and age, marital status, or level of education. Conclusion. Future research on the self-efficacy of parents of children with visual impairments and multiple disabilities should include analyses of specific areas of parental involvement, such as readiness to learn Braille, understanding needs related to visual functioning and environmental adaptation, as well as certain personality traits and intergenerational characteristics of parenting.